Prinsip Teologi Kelahiran Sebagai Model Konseling Kristen Kepada Pasangan Suami Istri Yang Belum Memiliki Anak - Guntur Hamonangan Sahat Silaban; Hery Budi Yosef (Sekolah Tinggi Teologi Sriwijaya, 2024)
The increasing number of problems experienced by married couples who do not have children among Christians such as loss of harmony, family violence, infidelity and divorce are important concerns for pastors in the Church. This study uses reference books and articles found through the internet with literature review and bibliological descriptive methods, namely making the Bible as a solution to solve problems that occur. So the conclusion is that household problems must be solved by applying a Christian counseling model based on the principles of Birth Theology. The model is a model of believing with a firm faith, a model of surrendering and repenting to God, a model of making a vow to ask God. The research results showed that through understanding the Theology of Birth which refers to understanding the concept of God as the initiator of birth, God helps the birth process and the birth of a child is a gift from God, and God is also the one who has power over married couples who do not or do not have children. However, Allah is willing to take into account efforts to have children. Thus, through Birth Theology with an approach to the model of faith, surrender, or repentance, even making a vow to God in the hope of obtaining it.